2021
DOI: 10.1002/jia2.25723
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year attrition and antiretroviral therapy response among HIV‐positive adults: a sex‐based cohort analysis from eight West African countries

Abstract: Introduction: Sex differences have already been reported in sub-Saharan Africa for attrition and immunological response after antiretroviral therapy (ART) initiation, but follow-up was usually limited to the first two to three years after ART initiation. We evaluated sex differences on the same outcomes in the 10 years following ART initiation in West African adults. Methods: We used cohort data of patients included in the IeDEA West Africa collaboration, who initiated ART between 2002 and 2014. We modelled no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Furthermore, this study suggested that male patients have higher risk of poor immune reconstitution and mortality than females, which may be traced back to differences in life customs, metabolism and adherence between males and females [36,37]. Kroeze et al[38] corroborated the above literature data.…”
Section: Resultssupporting
confidence: 53%
“…Furthermore, this study suggested that male patients have higher risk of poor immune reconstitution and mortality than females, which may be traced back to differences in life customs, metabolism and adherence between males and females [36,37]. Kroeze et al[38] corroborated the above literature data.…”
Section: Resultssupporting
confidence: 53%
“…As the period considered in our cohort study ended a few months after the implementation of the “Treat all” strategy in Madagascar, the impact of this strategy on attrition from care remains unclear. Furthermore, long-term retention in care remains a challenge, with a cumulative incidence of attrition from care of up to 75% 10 years after ART initiation among adult PLHIV in a study in Africa ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 490 PLHIV were included in the analysis; 67.1% (n = 329) were men. The median age (IQR) at enrollment in care was 29 years (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). We did not find any differences in age at enrollment in care between male and female PLHIV, with a median age (IQR) of 30 years (24-37) vs. 28 years (25-38) (p = 0.552), respectively.…”
Section: Plhiv Characteristics At Enrollment Into Hiv Carementioning
confidence: 99%
“…This is common with the finding of other studies, this may be due to the fact that female patients receive HAART at an early stage, reducing the incidence of opportunistic infections as well as achieving rapid CD4 cell recovery. In addition, traced back to differences in life customs, metabolism and adherence between males and females [ 38 , 39 ]. Kroeze et al [ 40 ] corroborated the above literature data.…”
Section: Discussionmentioning
confidence: 99%